ANALISIS KELENGKAPAN SARANA PEMBELAJARAN DALAM KETERAMPILAN PRAKTIK SISWA PADA PROGRAM AKUNTANSI (MYOB) SISWA KELAS XII - Riri Kaswari; Achmadi Achmadi; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine how much student skills in student practice in the accountingprogram (MYOB) Class XII students of the Accounting Departement at SMK Mandiri,Pontianak City. The form of this research is qualitative research with descriptive research type.The sample in this study were class XII students of Accounting Departement of Pontianak Cityindependent private vocational school for the 2019/2020 academic year, totaling 35 students.The sampling method is Total Sampling. The data were collected using observation sheets andthe results of the research carried out were the low completeness of learning facilities owned bythe Pontianak City independent private vocational school as evidenced by the inadequacy ofpractical tools with the total student total and then the low practical skills of students in theMYOB accounting program as evidenced by the student observations when doing the exercisesgiven and the resulting scores are still relatively lowKeywords: completeness of learning tools, accounting practice skills